Financial market contagion and the sovereign debt crisis: a smooth transition approach - Martins, Susana (2018)
In this paper, we investigate the timing and extent of sovereign debt contagion across nine Eurozone countries using daily returns on 10-year government bonds from 2007 until 2017. The novelty lies in modelling bond return correlations using a multivariate GARCH model with a multiplicative decomposition of the variance and time-varying conditional correlations. The model introduces flexibility by allowing the individual unconditional variances to be time-dependent and the correlations to change smoothly between two extreme states according to time and observable financial variables. The main results provide no evidence of asymmetric response of bond return comovements to negative shocks, as opposed to the size of innovations from the periphery which is expected to affect the dynamics of correlations. Our findings further indicate the presence of long-run contagion effects across peripheral countries following the more acute phase of the sovereign crisis. Interestingly, periods of high turbulence in the European stock market do not seem to drive financial contagion.